Gel electrolyte and preparation method and application thereof
By using amide polymerized monomers to help dissolve natural polymers and introducing biomass-based additives, the mechanical strength and ionic conductivity of the gel electrolyte are improved, the problem of insufficient gel electrolyte performance is solved, and the battery performance is improved and the process is improved. simplify.
Patent Information
- Application Number
- CN202410074316.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-18
- Publication Date
- 2025-01-24
AI Technical Summary
The low mechanical strength of gel electrolytes and the ionic conductivity are still different from that of liquid electrolytes, which affects the stability and performance of the battery.
Amide polymer monomers are used to help dissolve natural polymers to improve the mechanical properties of the gel, and biomass-based additives are introduced to enhance the coordination ability of lithium ions, thereby improving ionic conductivity.
The mechanical strength and ionic conductivity of the gel electrolyte are improved, the stability and cycle performance of the battery are enhanced, and the preparation cost and environmental pollution are reduced.
Smart Images

Figure CN119361810A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrolytes, and in particular to a gel electrolyte and a preparation method and application thereof. Background Art
[0002] As a key component of lithium-ion batteries, electrolytes play an important role in promoting ion conduction, maintaining charge balance, and forming stable interfaces. Traditional liquid electrolytes have defects such as high volatility, flammability, explosion, and leakage risks. Therefore, liquid electrolytes are gradually turning into solid electrolytes. The solid-liquid mixed gel electrolyte fixes a large amount of electrolyte in a polymer matrix, combining the good ion conduction ability of liquid electrolytes with the excellent safety and stability of solid electrolytes. It is considered an ideal choice for the transition to high-performance all-solid electrolytes.
[0003] However, the overall mechanical strength of the gel electrolyte is relatively low, which is not conducive to the stability of the battery during long-term operation, and the ionic conductivity is still lower than that of the liquid electrolyte, resulting in poor battery performance. Conventional modification strategies include designing polymer branched structures, introducing additives such as nanofillers and ionic liquids, etc., to improve the comprehensive performance of GPE. For example, patent CN114069036A discloses a gel electrolyte precursor and a preparation method thereof, which adds oxidized carbon nanoparticles to a polymer monomer containing double bonds to improve the ionic conductivity of the gel electrolyte, and is prepared by a step-by-step polymerization gel reaction. First, a gel electrolyte prepolymer is obtained by a primary polymerization, and then a cross-linking agent is added for a secondary polymerization gel reaction. The step-by-step method makes the gel polymerization more uniform, reduces the internal resistance of the battery, and improves the battery rate and cycle performance. CN110444807A discloses a method for preparing a composite gel polymer electrolyte, firstly using a first ionic liquid to evenly disperse the filler, then using a second ionic liquid as a polymerization monomer to prepare a gel polymer electrolyte by in-situ photopolymerization, so that the filler and the ionic liquid are stably and evenly dispersed in the polymer network to improve the mechanical strength, thermal stability, ionic conductivity and cycle performance of the composite gel. However, these methods have complicated procedures, and the additives are expensive and cause serious environmental pollution, making them difficult to apply to industrial production. Therefore, an ideal solution is needed. Summary of the invention
[0004] In order to improve the ionic conductivity of a gel electrolyte and simplify the modification process, the present invention provides a gel electrolyte and a preparation method and application thereof. Amide polymerization monomers are used to dissolve natural polymers, so that natural polymers with poor solubility and processing performance but excellent inherent performance are used as additives. The dissolving monomers improve the mechanical properties of the gel without having a negative impact on the electrochemical properties of the electrolyte. The introduced biomass-based additives have a large number of polar groups that can coordinate with lithium ions to improve the ionic conductivity of the gel electrolyte.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A gel electrolyte comprises the following raw materials: a first polymerizable monomer, a second polymerizable monomer, an additive and a conductive lithium salt; the first polymerizable monomer is a polyether acrylate monomer, the second polymerizable monomer is an acrylamide monomer, and the additive is a biopolymer.
[0006] Preferably, the first polymerizable monomer is at least one of polyethylene glycol acrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, neopentyl glycol diacrylate, and 1,6-hexanediol diacrylate.
[0007] Preferably, the second polymerizable monomer is at least one of acrylamide, diacetone acrylamide, methacrylamide, N,N-dimethylacrylamide, N-isopropylacrylamide and N-hydroxymethylacrylamide.
[0008] Preferably, the additive is at least one of carboxymethyl cellulose, cellulose acetate, cellulose diacetate, cellulose acetate butyrate and cellulose propionate.
[0009] Preferably, the conductive lithium salt is at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), tris(trifluoromethylsulfonyl)methyl lithium, and lithium trifluoromethylsulfonate.
[0010] The present invention also provides a method for preparing the gel electrolyte, comprising the following steps: S1. dispersing a conductive lithium salt in an organic solvent to obtain a liquid electrolyte; S2. After mixing the second polymerizable monomer and the additive, the mixture is added to the liquid electrolyte of S1 and mixed to obtain a mixed solution; S3. Evenly mix the first polymerizable monomer and the mixed solution of S2, and heat and polymerize under the action of an initiator to obtain a gel electrolyte.
[0011] Preferably, the organic solvent in step S1 is at least one of ethylene carbonate EC, propylene carbonate, dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, ethyl acetate, fluorobenzene, and ethyl acetoacetate; and / or; The initiator in step S2 is at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide and dicumyl peroxide. The above initiators can better promote the polymerization reaction. The mass of the initiator accounts for 0.01-1% of the total mass of the gel electrolyte. The polymerization reaction is controlled within a suitable rate range by using an appropriate amount of initiator; if the amount of initiator is too little, it is difficult to initiate and the reaction cannot proceed; if the amount of initiator is too much, the reaction speed is too fast and difficult to control.
[0012] Preferably, the mass ratio of the second polymerizable monomer to the additive in step S2 is (6-20):1; and / or; the mass ratio of the mixed solution of the first polymerizable monomer and S2 in step S3 is 1:(5-20). The second polymerizable monomer has a solubilizing effect on the biopolymer additive, and the first polymerizable monomer has good compatibility with the mixed solution of the second polymerizable monomer, the biopolymer additive and the liquid electrolyte.
[0013] Preferably, step S1 is specifically as follows: preparing a liquid electrolyte for a lithium-ion battery in an argon-filled glove box (water content <10 ppm, oxygen content <10 ppm), adding a conductive lithium salt to an organic solvent, and stirring with a magnetic stirrer for 15 to 60 minutes at a stirring speed of 600 to 1000 r / min to obtain a liquid electrolyte; and / or; Step S2 specifically comprises: mixing the second polymerized monomer with the additive, adding the mixture to the liquid electrolyte of S1, and stirring the mixture with a magnetic stirrer for 1 to 2 hours at a stirring speed of 600 to 1000 r / min to obtain a uniform mixed solution; and / or; Step S3 is specifically as follows: after magnetically stirring the mixed solution of the first polymerizable monomer, the initiator and S2 for 15 to 45 minutes to mix evenly, the mixed solution is placed in a forced air oven for heating at 30 to 75° C. for 1 to 72 hours to obtain a gel electrolyte.
[0014] The present invention also provides application of the gel electrolyte in a lithium ion battery, and the lithium ion battery is prepared by a one-step liquid injection-polymerization process.
[0015] Therefore, the beneficial effects of the present invention are: (1) Amide-based polymer monomers are used to dissolve natural polymers, so that natural polymers with low solubility and poor processing performance but excellent inherent properties can be used as additives. While improving the mechanical properties of the gel, the dissolving monomers do not have a negative impact on the electrochemical properties of the electrolyte.
[0016] (2) The introduced natural polymers are abundant in reserves, easy to obtain, low in cost, and can be naturally degraded, which is beneficial to environmental protection; natural polymer additives have a large number of polar groups that can coordinate with lithium ions to improve the ionic conductivity of the gel electrolyte; the long-chain structure of natural polymers and the interaction force between molecules make the gel electrolyte have good flexibility and strength, which can further enhance the mechanical properties of the gel electrolyte.
[0017] (3) The first polymerized monomer, the second monomer, the additive and the liquid electrolyte have similar structures, good compatibility and can form a uniform phase, thereby ensuring the uniformity and stability of the gel electrolyte.
[0018] (4) The preparation method of the present invention has low cost and simple operation. The gel electrolyte is prepared by a simple solution mixing method and can be injected into the battery cell in a one-step method to carry out a polymerization reaction. It can be directly used in the existing battery production process and solves the solid-solid interface contact problem in the use of solid electrolytes, thereby improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the mixed solution of S2 obtained in Example 1; Figure 2 is the gel electrolyte obtained in Example 1; Figure 3 This is the mixed solution of S2 obtained in Comparative Example 3, in which CA is not dissolved. DETAILED DESCRIPTION
[0020] The technical solution of the present invention is further described below through specific embodiments.
[0021] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art.
[0022] A gel electrolyte comprises the following raw materials: a first polymerizable monomer, a second polymerizable monomer, an additive, a conductive lithium salt, an organic solvent and an initiator.
[0023] The first polymerizable monomer is a polyether acrylate monomer, preferably at least one of polyethylene glycol acrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, neopentyl glycol diacrylate, and 1,6-hexanediol diacrylate.
[0024] The second polymerizable monomer is an acrylamide monomer, preferably at least one of acrylamide, diacetone acrylamide, methacrylamide, N,N-dimethylacrylamide, N-isopropylacrylamide and N-hydroxymethylacrylamide.
[0025] The additive is a biopolymer, preferably at least one of carboxymethyl cellulose, cellulose acetate, cellulose diacetate, cellulose acetate butyrate, and cellulose propionate.
[0026] The conductive lithium salt is at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), tris(trifluoromethylsulfonyl)methyl lithium, and lithium trifluoromethylsulfonate.
[0027] The organic solvent is at least one of ethylene carbonate EC, propylene carbonate, dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, ethyl acetate, fluorobenzene, and ethyl acetoacetate.
[0028] The initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide and dicumyl peroxide. The mass of the initiator accounts for 0.01-1% of the total mass of the gel electrolyte.
[0029] The present invention also provides a method for preparing the gel electrolyte, comprising the following steps: S1: Prepare a liquid electrolyte for lithium-ion batteries in an argon-filled glove box (water content <10 ppm, oxygen content <10 ppm), add a conductive lithium salt to an organic solvent, and stir with a magnetic stirrer for 15 to 60 minutes at a stirring speed of 600 to 1000 r / min to obtain a liquid electrolyte; S2: After mixing the second polymer monomer and the additive in a mass ratio of (6-20):1, add it to the liquid electrolyte of S1, stir it with a magnetic stirrer for 1-2 hours at a stirring speed of 600-1000 r / min to obtain a uniform mixed solution, such as Figure 1 As shown; S3: After the mixed solution of the first polymerization monomer, initiator and S2 is magnetically stirred for 15 to 45 minutes, Figure 2 As shown, the mixture is placed in a forced air oven at 30-75°C for 1-72 hours to obtain a gel electrolyte. The mass ratio of the first polymerizable monomer to the mixed solution of S2 is 1:(5-20); the mass of the initiator accounts for 0.01-1% of the total mass of the gel electrolyte.
[0030] The present invention also provides application of the gel electrolyte in a lithium ion battery, and the lithium ion battery is prepared by a one-step liquid injection-polymerization process.
[0031] Example 1 A gel electrolyte, the raw materials of which are: a first polymerizable monomer polyethylene glycol diacrylate, a second polymerizable monomer N,N-dimethylacrylamide DMAA, an additive cellulose diacetate CD, a conductive lithium salt LiPF6, an organic solvent EC+EMC+DMC, and an initiator azobisisobutyronitrile.
[0032] The preparation method is: S1. In an argon-filled glove box (water content <10ppm, oxygen content <10ppm), EC, EMC and DMC were mixed in a mass ratio of 4:10:1, and LiPF6 was added in a mass ratio of lithium salt to solvent of 1:5, and magnetic stirring was performed for 30min to completely dissolve LiPF6 to obtain a liquid electrolyte; S2. The second polymerized monomer DMAA, the additive CD and the liquid electrolyte of S1 were mixed in a mass ratio of 6:1:315, and magnetically stirred at a speed of 800 r / min at room temperature for 2 h to obtain a uniform mixed solution; S3. The mixed solution of the first polymerizable monomer polyethylene glycol diacrylate and S2 is mixed at a mass ratio of 1:12, and then a certain amount of initiator azobisisobutyronitrile is added, wherein the azobisisobutyronitrile accounts for 0.3% of the total mass of the gel electrolyte; after magnetic stirring for 30 minutes, the mixture is placed in a polytetrafluoroethylene bottle and placed in an oven at 45°C for reaction for 24 hours to obtain a gel electrolyte.
[0033] Example 2 The difference from Example 1 is that in step S2, the mass ratio of the second polymerizable monomer DMAA to the additive CD is 9:1.
[0034] A gel electrolyte, the raw materials of which are: a first polymerizable monomer polyethylene glycol diacrylate, a second polymerizable monomer N,N-dimethylacrylamide DMAA, an additive cellulose diacetate CD, a conductive lithium salt LiPF6, an organic solvent EC+EMC+DMC, and an initiator azobisisobutyronitrile.
[0035] The preparation method is: S1. In an argon-filled glove box (water content <10ppm, oxygen content <10ppm), EC, EMC and DMC were mixed in a mass ratio of 4:10:1, and LiPF6 was added in a mass ratio of lithium salt to solvent of 1:5, and magnetic stirring was performed for 30min to completely dissolve LiPF6 to obtain a liquid electrolyte; S2. The second polymerized monomer DMAA, the additive CD and the liquid electrolyte of S1 were mixed in a mass ratio of 9:1:315, and magnetically stirred at a speed of 800 r / min at room temperature for 2 h to obtain a uniform mixed solution; S3. The mixed solution of the first polymerizable monomer polyethylene glycol diacrylate and S2 is mixed at a mass ratio of 1:12, and then a certain amount of initiator azobisisobutyronitrile is added, wherein the azobisisobutyronitrile accounts for 0.3% of the mass of the gel electrolyte composition; after magnetic stirring for 30 minutes, the mixture is placed in a polytetrafluoroethylene bottle and placed in an oven at 45°C for reaction for 24 hours to obtain a gel electrolyte.
[0036] Example 3 The difference from Example 1 is that in step S2, the mass ratio of the second polymerizable monomer DMAA to the additive CD is 20:1.
[0037] A gel electrolyte, the raw materials of which are: a first polymerizable monomer polyethylene glycol diacrylate, a second polymerizable monomer N,N-dimethylacrylamide DMAA, an additive cellulose diacetate CD, a conductive lithium salt LiPF6, an organic solvent EC+EMC+DMC, and an initiator azobisisobutyronitrile.
[0038] The preparation method is: S1. In an argon-filled glove box (water content <10ppm, oxygen content <10ppm), EC, EMC and DMC were mixed in a mass ratio of 4:10:1, and LiPF6 was added in a mass ratio of lithium salt to solvent of 1:5, and magnetic stirring was performed for 30min to completely dissolve LiPF6 to obtain a liquid electrolyte; S2. The second polymerized monomer DMAA, the additive CD and the liquid electrolyte of S1 were mixed in a mass ratio of 20:1:315, and magnetically stirred at a speed of 800 r / min at room temperature for 2 h to obtain a uniform mixed solution; S3. The mixed solution of the first polymerizable monomer polyethylene glycol diacrylate and S2 is mixed at a mass ratio of 1:12, and then a certain amount of initiator azobisisobutyronitrile is added, wherein the azobisisobutyronitrile accounts for 0.3% of the mass of the gel electrolyte composition; after magnetic stirring for 30 minutes, the mixture is placed in a polytetrafluoroethylene bottle and placed in an oven at 45°C for reaction for 24 hours to obtain a gel electrolyte.
[0039] Example 4 A gel electrolyte, the raw materials of which are polyethylene glycol dimethacrylate as a first polymerizable monomer, diacetone acrylamide DAAM as a second polymerizable monomer, carboxymethyl cellulose as an additive, LiPF6 as a conductive lithium salt, EC+DEC as an organic solvent, and azobisisobutyronitrile as an initiator.
[0040] The preparation method is: S1. In an argon-filled glove box (water content <10ppm, oxygen content <10ppm), EC and DEC were mixed in a mass ratio of 4:1, and LiPF6 was added in a lithium salt and solvent mass ratio of 1:7. The liquid electrolyte was obtained by magnetic stirring for 30min to completely dissolve LiPF6. S2. The second polymerized monomer DAAM, the additive CD and the liquid electrolyte of S1 were mixed in a mass ratio of 6:1:315, and magnetically stirred at a speed of 800 r / min at room temperature for 2 h to obtain a uniform mixed solution; S3. The mixed solution of the first polymerizable monomer polyethylene glycol dimethacrylate and S2 is mixed at a mass ratio of 1:12, and then a certain amount of initiator azobisisobutyronitrile is added, wherein the azobisisobutyronitrile accounts for 0.3% of the total mass of the gel electrolyte; after magnetic stirring for 30 minutes, the mixture is placed in a polytetrafluoroethylene bottle and placed in an oven at 60°C for 2 hours to obtain a gel electrolyte.
[0041] Example 5 A gel electrolyte, the raw materials of which are first polymerized monomer polyethylene glycol dimethacrylate, additive cellulose acetate CA, conductive lithium salt LiPF6+LiPO2F2, organic solvent EC+EMC+DMC, and initiator azobisisobutyronitrile.
[0042] The preparation method is: S1. In an argon-filled glove box (water content <10ppm, oxygen content <10ppm), EC, EMC and DMC were mixed in a mass ratio of 1:1:1, and lithium salt was added in a lithium salt and solvent mass ratio of 1:5, wherein LiPF6:LiPO2F2=20:1, and magnetic stirring was performed for 30min to completely dissolve LiPF6 and LiPO2F2 to obtain a liquid electrolyte; S2. The second polymerized monomer DMAA, the additive CA and the liquid electrolyte of S1 were mixed in a mass ratio of 6:1:315, and magnetically stirred at a speed of 800 r / min at room temperature for 2 h to obtain a uniform mixed solution; S3. The mixed solution of the first polymerizable monomer polyethylene glycol dimethacrylate and S2 is mixed at a mass ratio of 1:12, and then a certain amount of initiator azobisisobutyronitrile is added, wherein the azobisisobutyronitrile accounts for 0.3% of the mass of the gel electrolyte composition; after magnetic stirring for 2 hours, the mixture is placed in a polytetrafluoroethylene bottle and placed in an oven at 35°C for reaction for 72 hours to obtain a gel electrolyte.
[0043] Comparative Example 1 The difference from Example 1 is that the raw material does not contain the second polymerizable monomer DMAA and the additive CD.
[0044] Comparative Example 2 The difference from Example 1 is that the raw material does not contain the additive CD.
[0045] Comparative Example 3 The difference from Example 1 is that the raw material does not contain the second polymerizable monomer DMAA.
[0046] Comparative Example 4 The difference from Example 1 is that in step S2, the mass ratio of the second polymerizable monomer DMAA to the additive CD is 4:1.
[0047] A gel electrolyte, the raw materials of which are: a first polymerizable monomer polyethylene glycol diacrylate, a second polymerizable monomer N,N-dimethylacrylamide DMAA, an additive cellulose diacetate CD, a conductive lithium salt LiPF6, an organic solvent EC+EMC+DMC, and an initiator azobisisobutyronitrile.
[0048] The preparation method is: S1. In an argon-filled glove box (water content <10ppm, oxygen content <10ppm), EC, EMC and DMC were mixed in a mass ratio of 4:10:1, and LiPF6 was added in a mass ratio of lithium salt to solvent of 1:5, and magnetic stirring was performed for 30min to completely dissolve LiPF6 to obtain a liquid electrolyte; S2. The second polymerized monomer DMAA, the additive CD and the liquid electrolyte of S1 were mixed in a mass ratio of 4:1:315, and magnetically stirred at a speed of 800 r / min at room temperature for 2 h to obtain a uniform mixed solution; S3. The mixed solution of the first polymerizable monomer polyethylene glycol diacrylate and S2 is mixed at a mass ratio of 1:12, and then a certain amount of initiator azobisisobutyronitrile is added, wherein the azobisisobutyronitrile accounts for 0.3% of the mass of the gel electrolyte composition; after magnetic stirring for 30 minutes, the mixture is placed in a polytetrafluoroethylene bottle and placed in an oven at 45°C for reaction for 24 hours to obtain a gel electrolyte.
[0049] Comparative Example 5 The difference from Example 1 is that in step S2, the mass ratio of the second polymerizable monomer DMAA to the additive CD is 50:1.
[0050] Comparative Example 6 The difference from Example 1 is that in step S3, the mixed solution of the first polymerizable monomer and S2 is mixed at a mass ratio of 1:1.
[0051] A gel electrolyte, the raw materials of which are: a first polymerizable monomer polyethylene glycol diacrylate, a second polymerizable monomer N,N-dimethylacrylamide DMAA, an additive cellulose diacetate CD, a conductive lithium salt LiPF6, an organic solvent EC+EMC+DMC, and an initiator azobisisobutyronitrile.
[0052] The preparation method is: S1. In an argon-filled glove box (water content <10ppm, oxygen content <10ppm), EC, EMC and DMC were mixed in a mass ratio of 4:10:1, and LiPF6 was added in a mass ratio of lithium salt to solvent of 1:5, and magnetic stirring was performed for 30min to completely dissolve LiPF6 to obtain a liquid electrolyte; S2. The second polymerized monomer DMAA, the additive CD and the liquid electrolyte of S1 were mixed in a mass ratio of 6:1:315, and magnetically stirred at a speed of 800 r / min at room temperature for 2 h to obtain a uniform mixed solution; S3. The mixed solution of the first polymerizable monomer polyethylene glycol diacrylate and S2 is mixed at a mass ratio of 1:1, and then a certain amount of initiator azobisisobutyronitrile is added, wherein the azobisisobutyronitrile accounts for 0.3% of the mass of the gel electrolyte composition; after magnetic stirring for 30 minutes, the mixture is placed in a polytetrafluoroethylene bottle and placed in an oven at 45°C for reaction for 24 hours to obtain a gel electrolyte.
[0053] Comparative Example 7 The difference from Example 1 is that azobisisobutyronitrile accounts for 2% of the total mass of the gel electrolyte.
[0054] A gel electrolyte, the raw materials of which are: a first polymerizable monomer polyethylene glycol diacrylate, a second polymerizable monomer N,N-dimethylacrylamide DMAA, an additive cellulose diacetate CD, a conductive lithium salt LiPF6, an organic solvent EC+EMC+DMC, and an initiator azobisisobutyronitrile.
[0055] The preparation method is: S1. In an argon-filled glove box (water content <10ppm, oxygen content <10ppm), EC, EMC and DMC were mixed in a mass ratio of 4:10:1, and LiPF6 was added in a mass ratio of lithium salt to solvent of 1:5, and magnetic stirring was performed for 30min to completely dissolve LiPF6 to obtain a liquid electrolyte; S2. The second polymerized monomer DMAA, the additive CD and the liquid electrolyte of S1 were mixed in a mass ratio of 6:1:315, and magnetically stirred at a speed of 800 r / min at room temperature for 2 h to obtain a uniform mixed solution; S3. The mixed solution of the first polymerizable monomer polyethylene glycol diacrylate and S2 is mixed at a mass ratio of 1:12, and then a certain amount of initiator azobisisobutyronitrile is added, wherein the azobisisobutyronitrile accounts for 2% of the mass of the gel electrolyte composition; after magnetic stirring for 30 minutes, the mixture is placed in a polytetrafluoroethylene bottle and placed in an oven at 45°C for reaction for 24 hours to obtain a gel electrolyte.
[0056] Performance Testing The gel electrolytes prepared in the examples and comparative examples were assembled into stainless steel / gel electrolyte / stainless steel batteries for ionic conductivity testing. The ionic conductivity was tested using the AC impedance method using a battery with a stainless steel / gel electrolyte / stainless steel structure. The ionic conductivity is given by the formula σ = d / (R b × S), where d represents the thickness of the gel electrolyte, S represents the contact area with the stainless steel sheet and the polymer electrolyte membrane, and R brepresents the body impedance measured by the AC impedance method. The results are shown in the following table.
[0057] As can be seen from Table 1, the ionic conductivity of Examples 1-3 gradually increases with the increase of the additive content, which effectively reduces the internal resistance and promotes the transmission of lithium ions. Comparative Examples 1-2 all show lower ionic conductivity, while Comparative Example 2 is slightly higher than Comparative Example 1. It can be seen that the addition of the second monomer not only improves the overall crosslinking degree and mechanical strength of the gel, but also promotes the transmission of lithium ions to a certain extent. Comparative Example 3 lacks the solubilizing effect of the second polymerized monomer, such as Figure 3 As shown, obvious undissolved CA particles were observed. In Comparative Example 4, due to the high relative value of the additive CD content, the viscosity is large, and the formed colloid is not well dispersed in the liquid electrolyte; in Comparative Example 5, due to the low additive content, the ionic conductivity is not significantly improved; in Comparative Example 6, due to the large amount of short-chain second polymerization monomers, the gel's liquid retention capacity is greatly reduced, the overall polymerization is poor, and a large amount of residual liquid is left; in Comparative Example 7, there are too many initiators, and the increase in solid content is not conducive to improving the ionic conductivity, and the reaction speed is fast, which is not conducive to the uniform dispersion of the electrolyte in the subsequent in-situ curing process. Comparing the embodiments and the comparative examples, it can be seen that the addition of the second monomer and the additive effectively improves the ionic conductivity of the gel electrolyte.
[0058] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A gel electrolyte, characterized in that: The method comprises the following raw materials: a first polymerizable monomer, a second polymerizable monomer, an additive and a conductive lithium salt; The first polymerizable monomer is a polyether acrylate monomer, the second polymerizable monomer is an acrylamide monomer, and the additive is a biopolymer.
2. A gel electrolyte according to claim 1, characterized in that: The first polymerizable monomer is at least one of polyethylene glycol acrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, neopentyl glycol diacrylate, and 1,6-hexanediol diacrylate.
3. A gel electrolyte according to claim 1, characterized in that: The second polymerizable monomer is at least one of acrylamide, diacetone acrylamide, methacrylamide, N,N-dimethylacrylamide, N-isopropylacrylamide and N-hydroxymethylacrylamide.
4. A gel electrolyte according to claim 1, 2 or 3, characterized in that: The additive is at least one of carboxymethyl cellulose, cellulose acetate, cellulose diacetate, cellulose acetate butyrate, and cellulose propionate.
5. A gel electrolyte according to claim 1, characterized in that: The conductive lithium salt is at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), tris(trifluoromethylsulfonyl)methyl lithium, and lithium trifluoromethylsulfonate.
6. The method for preparing the gel electrolyte according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. dispersing a conductive lithium salt in an organic solvent to obtain a liquid electrolyte; S2. After mixing the second polymerizable monomer and the additive, the mixture is added to the liquid electrolyte of S1 and mixed to obtain a mixed solution; S3. Evenly mix the first polymerizable monomer and the mixed solution of S2, and heat and polymerize under the action of an initiator to obtain a gel electrolyte.
7. The preparation method according to claim 6, characterized in that: The organic solvent in step S1 is at least one of ethylene carbonate EC, propylene carbonate, dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, ethyl acetate, fluorobenzene, and ethyl acetoacetate; and / or; The initiator in step S2 is at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide and diisopropylbenzene peroxide.
8. The preparation method according to claim 6, characterized in that: The mass ratio of the second polymerizable monomer to the additive in step S2 is (6-20):1; and / or; the mass ratio of the first polymerizable monomer to the mixed solution of S2 in step S3 is 1:(5-20); and / or; the mass of the initiator accounts for 0.01-1% of the total mass of the gel electrolyte.
9. The preparation method according to claim 6, 7 or 8, characterized in that: Step S1 specifically comprises: preparing a liquid electrolyte for a lithium-ion battery under an inert gas atmosphere, adding a conductive lithium salt into an organic solvent, and stirring with a magnetic stirrer for 15 to 60 minutes at a stirring speed of 600 to 1000 r / min to obtain a liquid electrolyte; and / or; Step S2 specifically comprises: mixing the second polymerized monomer with the additive, adding the mixture to the liquid electrolyte of S1, and stirring the mixture with a magnetic stirrer for 1 to 2 hours at a stirring speed of 600 to 1000 r / min to obtain a uniform mixed solution; and / or; Step S3 is specifically as follows: after magnetically stirring the mixed solution of the first polymerizable monomer, the initiator and S2 for 15 to 45 minutes to mix evenly, the mixed solution is placed in a forced air oven for heating at 30 to 75° C. for 1 to 72 hours to obtain a gel electrolyte.
10. Use of the gel electrolyte according to any one of claims 1 to 5 in a lithium ion battery, characterized in that: Lithium-ion batteries were prepared by a one-step liquid injection-polymerization process.
Citation Information
Patent Citations
Composite gel polymer electrolyte and preparation method and application thereof
CN110444807A
Cited By
Positive electrode additive, preparation method thereof, battery containing positive electrode additive and electric device
CN120757772A
Gel electrolyte and battery
CN120824420A